#TITLE_ALTERNATIVE# - P. RITONGA (NIM 12203017), BONA
From the previous study in this x field, we could obtained the value of critical reservoir pressure (CRP) and critical depletion pressure (CDP), then with this study we calculate the quantity of produced sand if the value is eksceeded. In this study a new important factor necessary for the estimation if the mount of free sand generated between sheared planes caused by the fluid drawdown was introduced. This factor is called sand production capability factor and was made by Musaed & Talal. Using correlation between CBHFP with depth we can predict the interval that potential become yielded zone, it is 4 zone and each zone of them was calculated it's sand production capability factor and it's volume of sand produced. The model for this calculation is a tube with intact zone ratio 1.72 and 1.16 (dimensionless for rw), where the radius of well that used is hypothetical 0.375 ft. The calculation show that for each yielded zone produce sand not more than 1 ft3. With this sudy we can predict the volume of sand produced so we can predict the optimum sand control method. The calculation show that the sand produced can be tolerated.